Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Solve the inequality.
2(4x
3) 2 -3(3x) + 5x?
O x 2 0.5
X 2 2
(-09 0.5]
(-c0, 2]


Sagot :

Answer:

Use the given functions to set up and simplify (-c⁰, 2]

Step-by-step explanation:

2(4x ⋅ 3) = 24x

2-3 (3x) + 5x = -4x + 2

Ox ⋅ 2 = 2Ox

0.5 = 2Ox

X ⋅ 2 = 2X

2 = 2X

-9 ⋅ 0.5 = -4.5

(-c⁰, 2] = (-1,2]

If this was helpful, let me know!